Enhancement of photon production from nonequilibrium disoriented chiral condensates - Prem Kumar (Physical Review D, 1997)
We study photoproduction during the non-equilibrium stages of the forma- tion of chiral condensates within the “quench” scenario of the chiral phase transition. The dynamics is modeled with a gauged linear sigma model. A novel quantum kinetic approach to the description of photoproduction far off equilibrium is developed. We find that non-equilibrium spinodal instabilities of long wavelength pion fluctuations are responsible for an enhanced photo- production rate for energies ≤ 80 MeV at order α. These non-equilibrium effects lead to a larger contribution than the typical processes in the medium, including that of the anomalous neutral pion decay π0 → 2γ (which is of order α2). We follow the evolution of the dynamics throughout the phase transition, which in this scenario occurs on a time scale of about 2.5−3 fm/c and integrate the photon yield through its evolution. The spectrum of photons produced throughout the phase transition is a non- equilibrium one. For thermal initial conditions at the time of the quench it interpolates between a thermal distri- bution about 6% above the initial temperature (at the time of the quench) for low energy ≤ 80 MeV photons, and a high energy tail in thermal equilibrium at the initial temperature, with a smooth crossover at 100 MeV. The rate displays a peak at ∼ 35 MeV which receives a larger enhancement the closer the initial temperature at the time of the quench is to the critical tempera- ture. It is found that the enhancement of photoproduction at low energies is not an artifact caused by the initial distribution of the photons, but is due to the pionic instabilities. We suggest that these strong out of equilibrium effects may provide experimental signatures for the formation and relaxation of DCC's in heavy ion collisions.